Analisis Implementasi Sistem Domisili dalam Penerimaan Murid Baru di SDN Kutorejo II Ditinjau dari Manajemen POAC (Planning, Organizing, Actuating, dan Controlling): Penelitian - Sri Fujianti; Ahmad Thohirin; Suyitno; A.Faizin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines the implementation of the domicile-based New Student Admission System (SPMB) at SDN Kutorejo II from a POAC management perspective. A qualitative descriptive approach was employed. Data were collected through observation, interviews, and document analysis involving the principal, admission committee, teachers, and staff. The findings indicate that planning was conducted in accordance with technical guidelines, organizing was carried out through task allocation, implementation proceeded in an orderly manner despite challenges in parental understanding, and controlling was implemented through internal evaluation and complaint follow-up. Overall, the implementation was fairly effective, although improvements in socialization and supervision are still needed.